A comparison of two turbulent dispersion parameterisations in the stable boundary layer using Lagrangian and Eulerian models - Moreira,Davidson Martins (2002)
An Eulerian model and a Lagrangian particle model are used to study the dispersion of a contaminant released from a low height source in the Stable Boundary Layer (SBL). The Eulerian model is based on the solution of the advection-diffusion equation by the Laplace transform technique. The Lagrangian model is based on a generalized form of the Langevin equation. Turbulence inputs are parameterised according to two procedures capable of generating continuous values in all stability conditions and in all heights of Planetary Boundary Layer (PBL). Statistical indices were calculated to compare the predicted and observed values of ground-level concentration. According to the statistical analysis, predicted concentration values agree well with the observed ones.